Millennium bcp : the recapitalization plan : a strategy case study - Pereira, Ana Margarida Cardoso (2019)
In 2012, Europe was affected by the economic crisis, conditioning companies’ performance. This environment led to changes in the consumers’ lifestyle, increasing the unemployment rate and decreasing the disposable income. Additionally, the banking sector has also suffered several transformations in its corporate governance. The present dissertation, presented in the form of a case study, aims to study the real case of Millennium bcp as a Portuguese bank affected by the economic crisis, having forced to resort the state aid. The reader has the opportunity to study the BCP strategy to overcome the recession period between 2012 and 2017. Therefore, the case has the purpose of study the Recapitalization Plan that the bank was submitted and the corresponding Restructuring Plan. BCP performed as a company that explored its resources and capabilities to establish competitive advantage, taking benefits from its reputation, culture, values, strategic objectives, the relationship with different stakeholders, the unique brand and the adaptation of its corporate governance model. Additionally, there is a reflection about the potential tensions between different stakeholders and their possible solutions based on Stakeholder Matrix Approach. Finally, since banking sector is extremely volatile the case also analyzes the future challenges faced by the bank, such as keeping the decision center in Portugal, the expansion of the brand and the development of digital services.